2010
DOI: 10.1016/j.jog.2010.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Satellite gravity gradiometry: Secular gravity field change over polar regions

Abstract: a b s t r a c tThe ESA Gravity and steady state Ocean and Circulation Explorer, GOCE, mission will utilise the principle of satellite gravity gradiometry to measure the long to medium wavelengths in the static gravity field. Previous studies have demonstrated the low sensitivity of GOCE to ocean tides and to temporal gravity field variations at the seasonal scale. In this study we investigate the sensitivity of satellite gradiometry missions such as GOCE to secular signals due to ice-mass change observed in Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…An important aspect of this study is that this new and robust feature of satellite gravity gradiometry is unveiled for the first time. While Moore and King [2010] predicted that GOCE cannot detect an Antarctic ice change, their proxy ice loss model employed smoothed GRACE solutions and reconstructed a vertical gradient change along the GOCE orbit. The procedure likely underestimated the signal strength in the GOCE sensitivity bandwidth.…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of this study is that this new and robust feature of satellite gravity gradiometry is unveiled for the first time. While Moore and King [2010] predicted that GOCE cannot detect an Antarctic ice change, their proxy ice loss model employed smoothed GRACE solutions and reconstructed a vertical gradient change along the GOCE orbit. The procedure likely underestimated the signal strength in the GOCE sensitivity bandwidth.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed simulation studies have confirmed that temporal gravity field variations generally remain far below the GOCE noise level (Jarecki et al 2005;Han et al 2006;Moore and King 2010). The extended mission duration now foreseen will hardly change this situation.…”
Section: Goce Versus Gracementioning
confidence: 92%